Psychosocial Functioning Among Caregivers of Childhood Cancer Survivors Following Treatment Completion. (7th August 2021) - Quast, Lauren F; Williamson Lewis, Rebecca; Lee, Jennifer L; Blount, Ronald L; Gilleland Marchak, Jordan
Abstract: Objective: To inform efforts to better support caregivers of children with cancer during the transition from treatment to survivorship, this study sought to characterize caregiver mental health-related quality of life (HRQOL) and anxiety, and examine the influence of family psychosocial risk and caregiver problem-solving on these outcomes. Method: Participants included 124 caregivers (child age M  =   10.05 years; SD = 4.78), 12–19 months from the conclusion of cancer-directed treatment. Participants' self-reported mental HRQOL, anxiety, and problem-solving were compared with community norms using t -tests. Correlations and hierarchical multiple regressions examined the influence of psychosocial risk and problem-solving on caregiver mental HRQOL and anxiety. Results: Overall, caregivers reported HRQOL and anxiety within normal limits. Caregivers also reported more adaptive patterns of problem-solving than community norms. Subsets of caregivers reported clinical levels of psychosocial risk (11%) and at-risk levels of mental HRQOL (2.5%) and anxiety (5.7%). Females reported greater anxiety than males. Psychosocial risk and negative problem orientation (NPO) were both related to poorer mental HRQOL and greater anxiety ( r = .40–.51, p 's < .001). Positive problem orientation related to better mental HRQOL and lower anxiety ( r = .18–.21, p 's < .05). Impulsivity/carelessness and avoidance were associated with greater anxiety ( r = .19–.25, p 's < .05). Only NPO accounted for additional variance in mental HRQOL and anxiety, over and above psychosocial risk and demographic characteristics. Conclusions: The majority of caregivers appear to be resilient and experience limited distress during the off therapy period. Targeting negative cognitive appraisals (NPO) through cognitive-behavioral therapy or problem-solving skills training may further improve caregiver psychosocial functioning.